A Genome‐Wide Association Study of Apple Quality and Scab Resistance. Issue 1 (1st March 2018) - McClure, Kendra A.; Gardner, Kyle M.; Douglas, Gavin M.; Song, Jun; Forney, Charles F.; DeLong, John; Fan, Lihua; Du, Lina; Toivonen, Peter M.A.; Somers, Daryl J.; Rajcan, Istvan; Myles, Sean
Abstract : The apple ( Malus × domestica Borkh.) is an economically and culturally important crop grown worldwide. Growers of this long‐lived perennial must produce fruit of adequate quality while also combatting abiotic and biotic stress. Traditional apple breeding can take up to 20 yr from initial cross to commercial release, but genomics‐assisted breeding can help accelerate this process. To advance genomics‐assisted breeding in apple, we performed genome‐wide association studies (GWAS) and genomic prediction in a collection of 172 apple accessions by linking over 55, 000 single nucleotide polymorphisms (SNPs) with 10 phenotypes collected over 2 yr. Genome‐wide association studies revealed several known loci for skin color, harvest date and firmness at harvest. Several significant GWAS associations were detected for resistance to a major fungal pathogen, apple scab ( Venturia ineaqualis [Cke.] Wint.), but we demonstrate that these hits likely represent a single ancestral source. Using genomic prediction, we show that most phenotypes are sufficiently predictable using genome‐wide SNPs to be candidates for genomic selection. Finally, we detect a signal for firmness retention after storage on chromosome 10 and show that it may not stem from variation in PG1, a gene repeatedly identified in bi‐parental mapping studies and widely believed to underlie a major QTL for firmness on chromosome 10. We provide evidence that this major QTL is more likely due to variation in a neighboring ethylene response factor (ERF) gene. The present study showcases the superior mapping resolution of GWAS compared to bi‐parental linkage mapping by identifying a novel candidate gene underlying a well‐studied, major QTL involved in apple firmness.